ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN DINI DI WILAYAH KERJA PUSKESMAS KAJUARA KABUPATEN BONE - Nasrayanti Nurdin; Hamdiyah; Resky Devi Akib; Ariyana (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Early marriage is marriage for teenagers under the age of 20 who should not be ready for marriage. Early marriage in the era of globalization now occurs in urban areas and does not deny that it is more prevalent in rural areas. Teenagers who marry young tend to be more difficult when it comes to adjusting and tend to be jealous of their friends and environment. This indicates that young married teenage couples will find emotional distress between them. Early marriage that occurs under the age of 19 years in a state of mental immaturity of a teenager will affect the acceptance of pregnancy in fact, minors cannot understand about sex and what its purpose is. This study aims to analyze the factors associated with early marriage in the working area of the Kajuara Health Center, Bone district. The type of research used is analytical observational research with a cross sectional study approach with the intention of knowing the relationship between one variable and another. This research has been carried out from July to August 2023. The population in this study was all married couples who married underage in the working area of the Kajuara Kbaupaten Bone Health Center as many as 40 respondents. The sampling technique is purposive sampling. The results of this study show that there is a mass media relationship, with early marriage obtained pvalue = 0.020. There is a relationship between education and early marriage pvalue = 0.000. There is a relationship between social environment and early marriage pvalue = 0.025.. It is hoped that the results of this study can be suggested to local health workers should further increase socialization to Kelurahan or Village in order to increase counseling on reproductive health in adolescents related to early marriage